NEW WAY OF ISOLATION OF ENZYME COMPLEX OF CHOLERA VIBRIO - PROTEOVIBRIN BY MEANS OF ULTRAFILTRATION - O. V. Gromova; I. A. Kuz'michenko; M. N. Kireev; S. A. Nizhegorodtsev; V. N. Korsukov (Acta Biomedica Scientifica, 2012)
The technology of isolation of the cholera vibrio complex of low-molecular enzymes related to pathogenicity factors, from cholera vaccine production wastes by means of concentrating ultrafiltration was developed. This technology allows to obtain standard series of the preparation termed proteovibrin which is free from the basic Vibrio cholerae immunogen - O-antigen, and possesses high activity of protease and. phospholipases A2 and. C. It is shown that proteovibrin is highly soluble in water and 0.14 molar NaCl solution, causes the production of antibodies in rabbits and is toxic for white mice. Its further examination seems to be promising, as well as its possible use as additional source of the cholera vibrio enzymes and. as tripsin-like preparation, applicable for protein raw material hydrolysis in production of microbiological nutrient media.